Has the impact of key determinants of German exports changed? Results from estimations of Germany's intra euro-area and extra euro-area exports - Kerstin Stahn (Deutsche Bundesbank, 2006)
The question as to whether changes in the external environment may have caused the importance of key determinants of German exports to shift since the 1990s is addressed by estimating Germany's exports to EMU partner countries (intra exports) and to countries outside the euro area (extra exports). Analytically, this is done first by estimating single-equation error correction models across different samples. Second, an estimation applying the Saikkonen (1991) approach is carried out to test whether the long-run export behaviour of intra and extra exports has changed since the 1990s. Finally, simulations are conducted by means of error-correction models in order to reconstruct the adjustment process of both intra and extra exports following demand and price shocks.
Keywords: F41; C22; 330; intra and extra euro-area exports; export demand; price competitiveness; error correction model; Export; Internationaler Wettbewerb; Schätzung; Deutschland